Using The Documentary Film “Sang Hyang Jaran: Teja Darmaning Kauripan” as A Medium For Preserving Traditional Art - I Nyoman Payuyasa; I Made Denny Chrisna Putra (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2022)
Arts and culture make Bali one of the world's tourist destinations. At first glance, it seems that Balinese art and culture are holding up well. In fact, various media reports that several art forms have become extinct, such as the Sang Hyang dance, the baris kraras dance, the wayang wong dance, and so on. Even in Karangasem, there are ten traditional arts that have become extinct. In Badung Regency, there are fifteen types of culture that are almost extinct, as well as in Buleleng and Denpasar. It is very important to save endangered art forms by using audio-visual media, especially documentary films. There is a documentary that is very interesting to study, namely a documentary entitled "Sang Hyang Jaran: Teja Darmaning Kauripan". This film records the re-embodiment of the art of the Sang Hyang Jaran dance in Sanur Kaja Village, which was once extinct. The problem studied in this study is how to use the documentary film "Sang Hyang Jaran: Teja Darmaning Kauripan" as a medium for preserving traditional arts? This research is a qualitative descriptive study using observation and interview data collection methods. Data analysis in this study used the Milles interactive model procedure with three stages of data analysis, namely (1) data reduction, (2) data presentation, and (3) verification or drawing conclusions. The result of this study is that the use of this film as a medium for preserving traditional arts can be seen from two elements, namely the first element is the visual element which includes the proactive observationalism and reactive observationalism, and the second element is verbal testimony.